2013
DOI: 10.1093/infdis/jit550
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy Reduces the Mycobacterium tuberculosis Burden in Human Macrophages and in Mice by Enhancing Autophagy and Phagosome Maturation

Abstract: These results suggest that statin-mediated reduction in cholesterol levels within phagosomal membranes counteract M. tuberculosis-induced inhibition of phagosomal maturation and promote host-induced autophagy, thereby augmenting host protection against tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
246
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(260 citation statements)
references
References 38 publications
5
246
2
1
Order By: Relevance
“…It has been recently documented that statins also have immunomodulatory and anti-inflammatory effects with reports of reduced mortality in patients with bacteremia (Kwak et al, 2000;Liao and Laufs, 2005;Tleyjeh et al, 2009;Parihar et al, 2014). In TB mice models, treatment with statins significantly reduced the bacterial load and the pulmonary pathological effects of TB infection (Parihar et al, 2014).…”
Section: Arg677trp (C2029t)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently documented that statins also have immunomodulatory and anti-inflammatory effects with reports of reduced mortality in patients with bacteremia (Kwak et al, 2000;Liao and Laufs, 2005;Tleyjeh et al, 2009;Parihar et al, 2014). In TB mice models, treatment with statins significantly reduced the bacterial load and the pulmonary pathological effects of TB infection (Parihar et al, 2014).…”
Section: Arg677trp (C2029t)mentioning
confidence: 99%
“…It was further shown in TB-infected macrophages and in mice models that treatment with statins improves the efficacy of first-line TB drug regimens and of rifampicin alone (Lobato et al, 2014;Skerry et al, 2014). It was demonstrated that statins improve bacterial clearance by the host and improve the efficacy of TB drugs by promoting autophagy through inhibition of the HMG-CoA reductase pathway (Parihar et al, 2014). Furthermore, there are some reports claiming that statins also enhance autophagy in an mTOR-dependent way by inhibiting the RAC1-mTOR signaling pathway (Wei et al, 2013).…”
Section: Arg677trp (C2029t)mentioning
confidence: 99%
“…Mtb (H37Rv) was grown to log phase in 7H9 complete media, and stocks were prepared for infections via an intranasal route as described previously. 50 Bacterial loads in lungs and spleen of Mtb-infected mice were determined at indicated time points after infection. Briefly, organs from killed mice were removed aseptically, weighed, and homogenized in 0.04% Tween-80.…”
Section: Methodsmentioning
confidence: 99%
“…Murine BMDMs and human MDMs were generated as previously described. 50 Macrophages were pretreated with either Ox-LDLs (100 mg ml À 1 ), native-LDLs (125 mg ml À 1 ), oleic acid (500 mM), palmitic acid (500 mM), or left untreated overnight. Cells were then infected in the presence of treatment(s) with Mtb (H37Rv, unless otherwise indicated) with multiplicity of infection of 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation